(untitled) (Research, Society and Development, 2020)
Removing original vegetation, irregularly waste dispositioning, increasing impermeable area on slopes, along with high rainfall, cause accidents that generate property damage and risk to people. Thus, the present study aims to assess the risk degree for a slope located in Olinda, Pernambuco, Brazil. As for the methodology, there was a site visit to assess factors that enhance the landslides followed by a quantitative analysis of the occupation dynamics at the site, through Qgis software, from 1975 to 2018. Finally, a qualitative analysis was carried out through the matrix of probability/consequence for risk assessment. Over time, the percentage of urban areas increased by 122.95% while the percentage of vegetation decreased by 55.40%. It was concluded that the environmental impacts affect or interfere at a median level. The anthropic actions most likely to have an impact on the area were: land use and occupation, sewage released directly into the soil, and vegetation cover suppression.